2022
DOI: 10.1002/jbm.b.35170
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan‐4 and stromal cell‐derived factor‐1 alpha functionalized endovascular scaffold facilitates adhesion, spreading and differentiation of endothelial colony forming cells and functions under flow and shear stress conditions

Abstract: Acellular vascular scaffolds with capture molecules have shown great promise in recruiting circulating endothelial colony forming cells (ECFCs) to promote in vivo endothelialization. A microenvironment conducive to cell spreading and differentiation following initial cell capture are key to the eventual formation of a functional endothelium. In this study, syndecan-4 and stromal cell-derived factor-1 alpha were used to functionalize an elastomeric biomaterial composed of poly(glycerol sebacate), Silk Fibroin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Previous studies in our laboratory have shown PFC to be an elastomeric composite material with compositional, structural, and mechanical similarities to coronary arteries [18]. PFC fabricated as small-diameter grafts had viscoelastic properties and performed mechanically under physiological flow and pressure [34]. In preliminary studies, it was demonstrated that platelets adhered to PFC fibers but were not activated compared to collagen fibers [18].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies in our laboratory have shown PFC to be an elastomeric composite material with compositional, structural, and mechanical similarities to coronary arteries [18]. PFC fabricated as small-diameter grafts had viscoelastic properties and performed mechanically under physiological flow and pressure [34]. In preliminary studies, it was demonstrated that platelets adhered to PFC fibers but were not activated compared to collagen fibers [18].…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study, we demonstrated syndecan-4 significantly enhanced the binding of growth factors to PFC and resulted in an increased capture of endothelial colony-forming cells (ECFCs) [33]. In a further study, we demonstrated syndecan-4 functionalization of PFC promoted spreading and differentiation of ECFCs [34].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation